2012
DOI: 10.5194/acpd-12-13201-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the relationship between total ozone and atmospheric dynamics and chemistry at mid-latitudes – Part 2: The effects of the El Niño/Southern Oscillation, volcanic eruptions and contributions of atmospheric dynamics and chemistry to long-term total ozone changes

Abstract: We present the first spatial analysis of "fingerprints" of the El Niño/Southern Oscillation (ENSO) and atmospheric aerosol load after major volcanic eruptions (El Chichón and Mt. Pinatubo) in extreme low and high (termed ELOs and EHOs, respectively) and mean values of total ozone for the northern and southern mid-latitudes (defined as the region between 30° and 60° north and south, respectively). Significant influence on ozone extremes was found for the warm ENSO phase in both hemisphere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 53 publications
5
22
0
2
Order By: Relevance
“…Its signature is nonetheless visible and significant in the eastern Pacific, where it contributes to up to 30% of the HNO 3 variability, and in the mid-latitudes of the Northern Hemisphere. The east-west gradient is in good agreement with chemical and dynamical effects of El Niño on O 3 , and with previous studies that showed the same patterns for the influence of the MEI on O 3 (Hood et al, 2010;Rieder et al, 2013;Wespes et al, 2017).…”
Section: The Solar Cycle Mei Ao/aao and Qbosupporting
confidence: 77%
See 2 more Smart Citations
“…Its signature is nonetheless visible and significant in the eastern Pacific, where it contributes to up to 30% of the HNO 3 variability, and in the mid-latitudes of the Northern Hemisphere. The east-west gradient is in good agreement with chemical and dynamical effects of El Niño on O 3 , and with previous studies that showed the same patterns for the influence of the MEI on O 3 (Hood et al, 2010;Rieder et al, 2013;Wespes et al, 2017).…”
Section: The Solar Cycle Mei Ao/aao and Qbosupporting
confidence: 77%
“…The impact of these oscillations on O 3 distributions has been demonstrated in several studies (e.g. Rieder et al, 2013;Wespes et al, 2016). We may expect a similar influence on the HNO 3 distributions, particularly because, even though they are tropospheric features, their phase and intensity affect the atmospheric circulation, and in particular the Brewer-Dobson Circulation, up to the stratosphere (Miller et al, 2006;Chehade et al, 2014).…”
Section: Arctic Oscillation and Antarctic Oscillationmentioning
confidence: 87%
See 1 more Smart Citation
“…Several recent studies (Frossard et al, 2013;Rieder et al, 2013aRieder et al, , 2013b have utilized extreme value theory (EVT) to characterize DM8H O 3 distributions since they are generally positively skewed (i.e. have long right-hand tails) and since state and federal agencies are particularly concerned with characterizing and controlling high ozone exceedances.…”
Section: Extreme Value Theory Analysismentioning
confidence: 99%
“…Several studies investigated the evolution of low ozone episodes at mid-latitudes (Anton et al 2008;Bojkov and Balis 2001;Brönnimann and Hood 2003;Fitzka et al 2014;Frossard et al 2013;Hood et al 2001;Iwao and Hirooka 2006;James 1998;Koch et al 2005;Krzyscin 2002;Newman et al 1988;Petzoldt 1999;Rieder et al 2010aRieder et al , b, 2011Rieder et al , 2013. The definitions for low ozone episodes, often referred to as ozone miniholes, vary among studies, and to date, only few studies have analyzed changes in the UV field during low ozone episodes and the general connection between low ozone episodes and UV levels (e.g., Anton et al 2008;Bartlett and Webb 2000;Fragkos et al 2016;MartinezLozano et al 2011;McKenzie et al 1991;Rieder et al 2010c).…”
Section: Introductionmentioning
confidence: 99%